2022
DOI: 10.1017/s1047951122001822
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with caregiver adherence to mobile health interstage home monitoring in infants with single ventricle or biventricular shunt-dependent heart disease

Abstract: Mobile health technology is an emerging tool in interstage home monitoring for infants with single ventricle heart disease or biventricular shunt-dependent defects. This study sought to describe adherence to mobile health monitoring and identify factors and outcomes associated with adherence to mobile health monitoring. This was a retrospective, single-institution study of infants who were followed in a mobile health-based interstage home monitoring programme between February 2016 and October 2020. The analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…To date, there is not a recommended level of adherence for monitoring of infants with SV heart disease; however, the degree of adherence in our study aligns with prior studies. 27 , 28 Jackson et al 28 reviewed adherence with mobile health monitoring of infants with SV heart disease at their institution during the interstage period. They defined high adherence as >50%, which was achieved in only 61% of their cohort, and found no association with adherence and interstage death.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is not a recommended level of adherence for monitoring of infants with SV heart disease; however, the degree of adherence in our study aligns with prior studies. 27 , 28 Jackson et al 28 reviewed adherence with mobile health monitoring of infants with SV heart disease at their institution during the interstage period. They defined high adherence as >50%, which was achieved in only 61% of their cohort, and found no association with adherence and interstage death.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Jackson et al identified lack of English language fluency, lower median household income, and Medicaid insurance as risk factors for lower caregiver adherence to mobile health interstage home monitoring. 43 Qualitative studies could provide valuable insight into obstacles to adherence and inspire alternative strategies to address disparities. In addition, the discontinuation of home monitoring following S2P marks a major transition point for infants with HLHS.…”
Section: Discussionmentioning
confidence: 99%